Reforming the current legal framework to enhance the preservation of endangered species - Faheema, Gatwiri Jaffer (Strathmore University, 2020)
The tourism industry is without a doubt a huge revenue earner for Kenya. Wildlife is a major tourist attraction and constitutes a large percentage of the tourism industry in Kenya. Therefore, Kenya has a responsibility to ensure protection of wildlife, being a national treasure that goes a long way in promoting the economy of the country, in addition to balancing the ecosystem. Efforts put in place by Kenya for the conservation and management of wildlife cannot go unnoticed. However, wildlife and specifically endangered species are still facing threats to date. The objectives of the research are to analyse the current legal framework with the aim of finding whether it is sufficient for the protection of endangered species and how it can be supplemented to enhance their preservation. It has critiqued a few sections in the Wildlife Conservation and Management Act that apply to the preservation of endangered species while identifying gaps in the provisions. The research has also identified the threats that endangered species face as a result to these gaps such as habitat loss and inadequate financing of conservation activities. Finally, through comparative analysis, the research has given recommendations that could reform the laws to enhance the preservation of endangered species. These include improving the identification and listing process and reconciling development projects with the preservation of endangered species
Submitted in partial fulfilment of the requirements of the Bachelor of Laws Degree, Strathmore University Law School